Mobile Integrated Healthcare: Preliminary Experience and Impact Analysis with a Medicare Advantage Population - Daniel J. Castillo; J. Brent Myers; Jonathan Mocko; Eric H. Beck (Journal of Health Economics and Outcomes Research)
**Background:** Mobile Integrated Healthcare (MIH) is a novel, patient-centered approach to population management. This concept creates a needs-matched, time appropriate assignment of one or more members of a multi-professional clinical team to care for patients on a scheduled or unscheduled basis. The selection of the site of care for scheduled interventions is driven by patient choice and, most often occurs in the patient’s home; unscheduled interventions are guided by a 5-point triage system and, based on acuity, may be treated in the home, primary care office, urgent care or, rarely, in an emergency department.